Effects of crystalline phase formation of multiferroic BiFeO3 on microwave absorption characteristics - Siti Nor Ain Rusly; Khamirul Amin Matori; Ismayadi Ismail; Zulkifly Abbas; Zaiki Awang; Fadzidah Mohd Idris; Idza Riati Ibrahim (Springer Science+Business Media, LLC., 2024)
This paper reports a study of the microwave absorption properties of multiferroic BiFeO3 (BFO) epoxy resin composites. The effects of various sintering temperatures on the crystalline phase of BFO and its microwave absorption characteristics were critically analyzed. BFO nanoparticles were synthesized by mechanical activation high energy ball milling (HEBM) with post heat treatment over various temperatures ranging from 700 to 800 C. The XRD results showed by using the HEBM method, BFO phase is formed at a lower sintering temperature of 700 C compared to conventional solid state reaction due to the enhanced diffusion rates. The phase composition and the grain sizes had significant influence on the permeability, permittivity and reflection loss values of BFO composites measured by a network analyzer in the frequency range from 8 to 18 GHz. It was observed that the purity fraction of BFO phase and the grain sizes increased with the sintering temperature. By increasing the sintering temperature up to 775 C, the microwave absorption properties were enhanced over a broad working frequency range corresponding to the reflection loss below ? 10 dB (i.e. 90% absorption) due to crystalline phase changes. BFO samples sintered at 775 C demonstrated higher absorption ability with RLmin ? 40.5 dB over a 1.31 GHz bandwidth, showing that BiFeO3 has great potential as a microwave absorbing material.